2002
DOI: 10.1038/sj/jim/7000247
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of Streptomyces violaceusniger strain G10 on Fusarium oxysporum f.sp. cubense race 4: Indirect evidence for the role of antibiosis in the antagonistic process

Abstract: Fusarium oxysporum f.sp. cubense is the causal pathogen of wilt disease of banana. A cost-effective measure of control for this disease is still not available. Streptomyces violaceusniger strain G10 acts as an antifungal agent antagonistic towards many different phytopathogenic fungi, including different pathogenic races of the Fusarium wilt pathogen. In an attempt to understand the mode of action of this antagonist in nature, the interaction between S. violaceusniger strain G10 and F. oxysporum f.sp. cubense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 28 publications
1
56
0
1
Order By: Relevance
“…Inhibitory effects such as lysis, inhibition of fungal spore germination, and growth malformations like swelling, hyphal protuberances and abnormal branching of hyphae generally produced by antifungal metabolites [3], were observed in strain-g10-amended soil [14]. The latter study also showed that very few conidia were formed from the remains of undamaged Foc mycelium.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Inhibitory effects such as lysis, inhibition of fungal spore germination, and growth malformations like swelling, hyphal protuberances and abnormal branching of hyphae generally produced by antifungal metabolites [3], were observed in strain-g10-amended soil [14]. The latter study also showed that very few conidia were formed from the remains of undamaged Foc mycelium.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism(s) associated with the antagonistic effects of strain g10 against Foc race 4 in a soil environment was studied previously [14]. Inhibitory effects such as lysis, inhibition of fungal spore germination, and growth malformations like swelling, hyphal protuberances and abnormal branching of hyphae generally produced by antifungal metabolites [3], were observed in strain-g10-amended soil [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal hyphae were marked with broken, lytic, rolled, twisted, curled and abnormal branching of hyphae (Figure 2). Getha and Vikineswary (2002) reported that hyphal distortion like lytic of hyphal ends, swollen hyphae, abnormal branching of hyphae and the formation of hyphal protuberances is observed after contacted Fusarium oxysporum f.sp. cubense hyphae with Streptomyces violaceusniger strain G10.…”
Section: Observation Of Hyphal Abnormalitymentioning
confidence: 99%
“…Furthermore, these approaches can induce an outbreak of Panama disease, a type of banana Fusarium wilt, caused by the fungal pathogen Fusarium oxysporum. Infection poses serious problems because the pathogen is resistant to fungicide and cannot be controlled chemically (Getha and Vikineswary 2002;Xiao et al 2013). It would therefore be highly useful if the biomass from banana stems could be converted into useful biogas, which would simultaneously solve any environmental or pathogen-related problems.…”
Section: Introductionmentioning
confidence: 99%